Pengaruh Pengendalian Internal Pada Efisiensi Kredit Di Lembaga Perkreditan Desa (LPD) Se-Kecamatan Sukawati Kabupaten Gianyar - Wilatini, Kadek Ari Dyah; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p04, 2019)
The purpose of this research was to obtain empirical evidence of the influence of internal  control elements on the efficiency of lending in the LPD of Sukawati district, Gianyar  Regency. The data used in this research are primary in the form of questionnaire answers  and secondary data in the form of non performing loan. The sampling uses a saturated  sample technique. The sample used was 33 LPDs in Sukawati district. The analysis   technique used was multiple linier regression. Based on analysis concluded that  environment control, risk assessment, control activities, and monitoring have a positive  effect on the lending efficiency, while the information and communication has negative  effect on lending efficiency. Keyword: Internal control, lending efficiency, LPD.